y’’’’ - 2*y''' + 2*y'' = 3*e^(-x) + e^(-x)*sin(x) + 2*x*e^(-x)
£^4-2£^3+2£^2=0
£^2(£^2-2£+2)=0
£=0
£^2-2£+2=0
d=4-8=-4
£=(2+2i)/2=1+i
£=(2-2i)/2=1-i
y(1)=C1 e^(0x)+ e^(x)(C3cosx+C4sinx)=C1+ (C3cosx+C4sinx)e(x)
y(2)=Ae(-x)+Be^(-x)sin(x)+Dxe^(-x)
y’=-Ae^(-x)+B(-e^(-x)sinx+ e^(-x)cosx)+D(-xe^(-x)+e^(-x)
y’’=Ae^(-x)+B(-2 e^(-x)cosx)+D(x-2) e^(-x)
y’’’=-A e^(-x)+2B e^(-x)(sinx+cosx) +D(3-x) e^(-x)
y’’’’=A e^(-x)-4Bsinx e^(-x)+D(x-4) e^(-x)
A e^(-x)-4Bsinx e^(-x)+D(x-4) e^(-x)-2(-A e^(-x)+2B e^(-x)(sinx+cosx) +D(3-x) e^(-x))+2(Ae^(-x)+B(-2 e^(-x)cosx)+D(x-2) e^(-x))= 3*e^(-x) + e^(-x)*sin(x) + 2*x*e^(-x)
A=688/400
B=(-25+25ctg(x))/400
D=C/e^(-x)+2/5
y(1)=C1+e^x(C3sinx+C4cosx)
y(2)=688/400e^(-x) +1/400e^(-x)(-25sinx +25cosx)+x(C(2)+2/5e^(-x))
y=y(1)+y(2)
Comments
Leave a comment